2017
DOI: 10.3354/meps12150
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coral sensitivity to thermal anomalies

Abstract: The 1998 and 2016 thermal anomalies were among the 2 most severe global-scale anomalies in recent history, with broad-scale impacts on reef condition. In 2 Kenyan fully protected national park reef lagoons, the water flow, light, and temperature exposure severity of these 2 events was grossly similar at 7.3 cm s -1 , ~50 Einsteins m −2 d −1 and ~85 degree-days above summer baseline. Yet, despite similarities in the coral communities' metrics over this time, the bleaching responses were diminished considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 76 publications
4
66
2
Order By: Relevance
“…Only two species of the fifteen most common (P. astreoides and S. intersepta) experienced a slight increase in total colony mortality in 2015; however, the uptick was \ 2.0% for both these species when all other species saw reductions in total colony mortality from 2014 to 2015. Although the idea that corals can be less impacted by a second bleaching event may seem counterintuitive, this has been documented before in the eastern tropical Pacific, the Great Barrier Reef, French Polynesia, SE Asia, the Maldives, and Kenya (Glynn et al 2001;Maynard et al 2008;Thompson and van Woesik 2009;Guest et al 2012;Pratchett et al 2013;McClanahan and Muthiga 2014;McClanahan 2017). Other studies have reported the more intuitive trend of compounded impacts from repeated thermal stress events (e.g., Neal et al 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Only two species of the fifteen most common (P. astreoides and S. intersepta) experienced a slight increase in total colony mortality in 2015; however, the uptick was \ 2.0% for both these species when all other species saw reductions in total colony mortality from 2014 to 2015. Although the idea that corals can be less impacted by a second bleaching event may seem counterintuitive, this has been documented before in the eastern tropical Pacific, the Great Barrier Reef, French Polynesia, SE Asia, the Maldives, and Kenya (Glynn et al 2001;Maynard et al 2008;Thompson and van Woesik 2009;Guest et al 2012;Pratchett et al 2013;McClanahan and Muthiga 2014;McClanahan 2017). Other studies have reported the more intuitive trend of compounded impacts from repeated thermal stress events (e.g., Neal et al 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Laboratory studies have shown that back-to-back bleaching can turn some coral species thought to be winners, or resistant to heat stress, into losers and vice versa (Grottoli et al, 2014). Multiple studies have shown that corals are often less impacted by a second bleaching event when events are separated by several or more years (Glynn, Maté, Baker, & Calderon, 2001;Guest et al, 2012;Maynard, Anthony, Marshall, & Masiri, 2008;McClanahan, 2017). Yet, other studies have observed the expected pattern of additive, negative impacts with multiple bleaching events (Neal et al, 2016;Riegl & Purkis, 2015).…”
Section: Benthic Cover After Bleaching Recoverymentioning
confidence: 99%
“…3) 30 . This raises the question of whether coral holobionts can be trained or modified to increase their damage thresholds and become better able to survive thermal extremes 6,77 .
Fig. 3Damage threshold hypothesis ( a ) during a thermal bleaching event comparing how a tolerant and a suscpetible holobiont may respond, and ( b ) a potential mechanism for immune memory through mulitple perturbations
…”
Section: Coral Bleaching and Breaching The Damage Thresholdmentioning
confidence: 99%